2013
DOI: 10.1002/mame.201200433
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Graphene and Carbon Materials as Additives for Melt‐Extruded Flame Retardant Polypropylene

Abstract: Functionalized graphene nanosheets TRGO and MLG 250, prepared from thermally reduced graphite oxide, represent attractive carbon additives for improving the performance of flame retardant polypropylene (PP‐FR). The influence of carbon nanofiller type and content on morphology, thermal, mechanical, and electrical properties as well as the fire behavior of melt‐extruded PP‐FR is investigated. In contrast to conventional nano‐ and micron‐sized carbon fillers such as expanded graphite (EG 40), nano‐scaled carbon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 56 publications
(131 reference statements)
7
64
0
Order By: Relevance
“…n.d., not determined. The bulk conductivity of CB and CNT was not measurable owing to the inherent test specimen brittleness; values for CNT, CB, and pristine graphite are adapted from previous publications …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…n.d., not determined. The bulk conductivity of CB and CNT was not measurable owing to the inherent test specimen brittleness; values for CNT, CB, and pristine graphite are adapted from previous publications …”
Section: Methodsmentioning
confidence: 99%
“…The pure carbon compounds were characterized by bulk conductivity measurements using compression‐molded specimens (7.4 kbar, pressure detention period 2 min, specimen diameter 13 mm, specimen thickness 0.30–0.45 mm). The electrical filler resistivity was detected by a four‐point measurement (electrode distance 2.5 mm) and converted into specific electrical conductivities, taking into account a correction factor regarding the spherical sample geometry . The resistivity of carbon filler/PA 12 nanocomposites was detected using injection molded DMA test specimens (50 × 6 × 2 mm 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Dittrich et al [30] and Hofmann et al [43] incorporated layered highly exfoliated thermally reduced graphene (TRGO), layered minor exfoliated-expanded graphite (EG40), spherical carbon black (CB) and multiwall carbon nanotubes (MWNT) into polypropylene (denoted as PP) at various concentrations between 0.5 and 7.5 %. They found that the effect of the fillers on the thermal stability, flow behaviour, burning behaviour and flame resistance of the polymer depends on the concentration and morphology of the fillers.…”
Section: Graphene and Graphene Oxide Flame Retardantsmentioning
confidence: 99%
“…The data for ignition time (IT), peak of heat release rate (PHRR), total heat released (THR) and total smoke production (TSP) was taken at flameout. Flameout was defined as the extinguishment of the visible yellow flame [23]. The density of PIFs after the postcuring process was determined by drainage method.…”
Section: Characterizationmentioning
confidence: 99%